Jewish ethnic identity and relations in Hellenistic Egypt: with walls of iron? - Moore, Stewart Alden (Supplements to the Journal for the study of Judaism, 2015)
Contents -- Acknowledgments -- Abbreviations -- Introduction -- Chapter 1. Thicker than Water? A Social-Scientific Approach to Ancient Judean Ethnicity -- 1. The Early Dominant Paradigm of Ethnicity -- 2. The Use and Abuse of Ethnicity in Second Temple Studies -- 3. Beyond the Durkheimian Approach -- 4. Conclusions -- Chapter 2. The History of Dustbins: Reconstructing Ethnicity from the Papyri -- 1. Models of Greek-Egyptian Interaction -- 2. Models of Greek-Egyptian Conflict -- 3. Judean Ethnic Markers in the Papyri -- 4. Conclusions